1997
DOI: 10.1111/j.1600-0447.1997.tb09933.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and myoclonus associated with antidepressant treatment: assessment of potential risk factors, including CYP2D6 and CYP2C19 polymorphisms, and treatment with CYP2D6 inhibitors

Abstract: All adverse drug reaction reports labelled seizures or myoclonus during treatment with antidepressants and stored in the Swedish national database for spontaneous reporting of adverse drug reactions were reviewed in order to evaluate possible risk factors. The reporting physicians were contacted and asked for complementary information, and blood samples for determination of the CYP2D6 and CYP2C19 genotypes were obtained from patients available. In total, 25 cases of seizures and 7 cases of myoclonus were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…A Medline review of the literature revealed an association between myoclonus and antidepressant agents including SSRIs (Spigset et al 1997). …”
Section: Introductionmentioning
confidence: 98%
“…A Medline review of the literature revealed an association between myoclonus and antidepressant agents including SSRIs (Spigset et al 1997). …”
Section: Introductionmentioning
confidence: 98%
“…Few studies provide quantitative data on adverse drug reactions. 49 induced seizures was reported in relation to CYP2D6 activity 145 and several studies showed a relationship between extrapyramidal side effects of antipsychotic drugs and CYP2D6 polymorphisms. 96,[146][147][148][149][150][151][152][153][154][155][156] However, compared to the large efforts made to evaluate pharmacokinetic differences due to CYP polymorphisms, few prospective studies on benefit of phenotyping or genotyping for therapeutic outcome have been conducted so far.…”
Section: Impact Of Cyp2c9mentioning
confidence: 99%
“…While tightly controlled study designs can highlight the influence of genetic variation on drug disposition, they may overstate or miss the true relevance of genetic variation where it may matter most, in the clinical environment. Several studies have attempted to relate CYP2C19 PM phenotype to xenobiotic toxicity [88][89][90][91][92]. However, only one study actually associated CYP2C19 PM phenotype with drug toxicity.…”
Section: Effects Of Cyp2c19 Polymorphism On Drug Metabolism and Responsementioning
confidence: 99%